Análisis de la participación ciudadana y su actuación en los procesos de control social de los medios de comunicación: diario La Hora y Ecotel TV de la ciudad de Loja, periodo marzo – julio 2015 - Hidalgo Pineda, María José (2016)
Given the importance that today has communication within contemporary everyday life of people it is essential to display not only as an issue that only professionals or interested persons connected with communication; therefore it must become a social and citizen challenge that link directly to building laws, to collect the true feel of a population and not start from an assumption that divise from a parliamentary tribune. Many of these rules should reflect the struggle that social groups have been fighting for years. The community involvement in the development of communication processes should begin to display more media whether public, private or community, is why this research paper seeks to learn the tools of participation using the media Diario La Hora and Ecotel Tv city of Loja, also observe the control mechanism using the Council of Citizen Participation and Social control and the Superintendency of Communication, likewise reflects the feeling of the lojana citizens against the phenomenon of citizen participation. After a diagnosis that develops through techniques applied during the investigation which was evident low participation and poor mechanisms that do not allow citizens to build a participatory, critical and joint construction communication, which led to proposing an alternative proposal it is the development of a Citizen Observatory of Communication. Keywords: Community communication, participatory communication, democracy, public opinion, public participation.